Photoinduced Ligand-to-Metal Charge Transfer in Base-Metal Catalysis - Treacy, Sean M.; Rovis, Tomislav (Synthesis, 2023)
The absorption of light by photosensitizers has been shown to offer novel reactive pathways through electronic excited state intermediates, complementing ground-state mechanisms. Such strategies have been applied in both photocatalysis and photoredox catalysis, driven by generating reactive intermediates from their long-lived excited states. One developing area is photoinduced ligand-to-metal charge transfer (LMCT) catalysis, in which coordination of a ligand to a metal center and subsequent excitation with light results in the formation of a reactive radical and a reduced metal center. This mini review concerns the foundations and recent developments on ligand-to-metal charge transfer in transition-metal catalysis, focusing on the organic transformations made possible through this mechanism.1 Introduction2 Iron3 Cobalt4 Nickel5 Copper6 Future Outlook and Conclusion
Keywords: ligand-to-metal charge transfer; photocatalysis; base-metal catalysis; organic synthesis; photochemistry; photoredox catalysis